La gestión municipal y su impacto en el desarrollo de los gobiernos locales del país - García Carranza, Jesús Alfonso (2010)
The following PHD thesis, will analyze the municipal gestion and their impact of the Peru’s local government development, which is an estimate projected financial, usually in the form of annual income and expenditure of local government, necessary to comply with the purposes of proper planning. Also is a basic tool for the operational implementation of the decisions of economic policy. It is a document that reflects the impact of management in the development of local governments. This will be made, by studying the objectives and goals of each organization that has been chosen by chance, in the economic year. This is the base for develop and expose a group of gestion instruments that will help to make real, all the objectives that have been made, in the gestion documents of these organizations. Assuming the target of the municipal organization to satisfy people’s necessities to improve their quality of life, the chance for this to happen depends of the ability of them to use it in a proper way, all the resources, making it with efficient. The Municipal is the oldest organization that had been existed until know. This is essential for a democratic life and also is the institutional cell of a country where people living at the same land have problems that must be attended to figure it out, that is the reason the municipal organization have been created.